Pressure‐Temperature‐Deformation‐Time Constraints on the South Tibetan Detachment System in the Garhwal Himalaya (NW India). Issue 11 (3rd November 2017) - Iaccarino, S.; Montomoli, C.; Carosi, R.; Montemagni, C.; Massonne, H.‐J.; Langone, A.; Jain, A. K.; Visonà, D.
Abstract: A peculiar feature of the Himalaya is the occurrence of a system of low‐angle normal faults and shear zones, the South Tibetan Detachment System (STDS), at the mountain crests. The STDS was active during synconvergent tectonics. We describe the STDS‐related sheared rocks along the Dhauli Ganga valley, in the Garhwal Himalaya (NW India), where the Malari granite, reported as an undeformed igneous body crosscutting the STDS, occurs. A detailed multidisciplinary study, integrating field‐based, microstructural, petrographic, and geochronological analyses, was carried out on rocks along this valley. We demonstrate how the noncoaxial ductile portion of the STDS affected the upper part of the Greater Himalaya Sequence migmatite, which experienced peak pressure (P)‐temperature (T) conditions of 0.9–1.1 GPa and ≥750°C at ≥24 Ma. This migmatite has been reworked structurally upward leading to the formation of high‐T sillimanite‐bearing mylonites. Further upward, medium‐T shearing deformed the Malari granite and leucogranite dykes, forming medium‐T mylonites. Ductile shearing was temporally constrained, based on new in situ monazite datings and previously published Ar‐Ar geochronology, between ~20 and 15 Ma. We demonstrate that a preserved ductile to brittle spatial and temporal transition of the STDS deformation exists, with the brittle features overprinting ductile ones. Our data shed new light on the geological evolution of the STDS in the NW Himalaya with implications for the relationship and relative timing of partial melting, granite emplacement, and deformation along low‐angle normal faults. Key Points: P‐T‐D paths and in situ geochronology allowed us to unravel the history of a LANF in the Higher Himalaya High‐temperature mylonite along the South Tibetan Detachment, North India, developed after the rock experienced P  ~ 1.0 GPa and T  ≥ 750°C Ductile shearing of the STDS is constrained at ~20–15 Ma; brittle deformation overprinted mylonite after ~15 Ma